Interethnic Relations and the Protection of Minority Rights in Serbia - Danijela Gavrilović (Migracijske i Etniĉke Teme, 2011)
Serbia, as a multiethnic and multiconfessional community, still faces the issue of establishing social relations which are based on non-discrimination in all matters, as well as ethnic belonging. The heritage of ethnic conflicts and the as-yet unresolved relations in Kosovo still present potential negative factors for establishing ethnic relations on the principles of equality, but also of trust and safe coexistence. As one of more important identifiers of ethnic belonging and relations between religious communities in the Balkans, religion also represents obstacles in Serbia as a multireligious community. The first part of this text analyses data from sociological research projects, which point to the content and quality of multiethnic relations in Serbia. The second step is the analysis of the legal framework in this area which is being improved in Serbia with the aim of achieving equality between ethnic groups and co-existence founded on trust and nondiscrimination. The third step is the review of some examples in Serbia of discrimination based on ethnic belonging.